Acid/base reversible allochroic anthocyanin/palygorskite hybrid pigments: Preparation, stability and potential applications. (December 2019) - Li, Shue; Ding, Junjie; Mu, Bin; Wang, Xiaowen; Kang, Yuru; Wang, Aiqin
Abstract: The color of natural anthocyanin is sensitive to acid or base atmosphere, and thus it may be used as an intelligent acid/base-responsive allochroic pigment. However, the instability of anthocyanin to external environments severely limits their relevant applications. In this study, the organic/inorganic hybrid pigment is facilely prepared by adsorption of anthocyanin extracted from fresh blueberry using palygorskite followed by a grinding process. The effect of grinding time on the thermal and the chemical stabilities of hybrid pigment was studied, and it is found that the grinding process can promote the diffusion of anthocyanin molecules into the external grooves of palygorskite, which favors the improvement of the stability of natural anthocyanin to external environments. In addition, the colors of the resulting hybrid pigments transform from pale pink to steel gray with the change of atmosphere from acid to base. The effect of the added amounts of hybrid pigments on mechanical properties of sodium alginate films are investigated, and the results indicate that the incorporation of hybrid pigments obviously improve the tensile strength and elongation at break of sodium alginate films. Graphical abstract: Image 1 Highlights: Reversible acid/base chromism hybrid pigments were prepared using natural CAN and PAL. Grinding process favors ACN to enter into external grooves of PAL. The thermal and chemical stabilities of ACN were significantly improved. Hybrid pigments exhibited good reversible chromism to external acid/base atmospheres. The mechanical properties of ACN/PAL/SA nanocomposite films are improved remarkably.